2020
DOI: 10.1038/s41598-020-60308-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a molecular marker associated with lignotuber in Eucalyptus ssp

Abstract: About 95% of Eucalyptus species present an organ known as a lignotuber, a basal woody swelling that holds a large number of dormant buds in a protected position along with carbohydrates and other nutrients. The importance of this trait in Eucalyptus species relates to its regenerative capacity, particularly in the context of coppicing practices and survival in regions of high abiotic stress, especially fire. In this study, we identified and characterized a genomic region associated with the lignotuber trait in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The reason for the divergent trends in heritability between sites is unclear and may be driven by the different environmental conditions at the three trials and contrasts with the findings from Osorio et al (2001) who found for E. grandis that heritabilities of tree volume and mean annual increments increased from 3 years old until 6 years old (harvest age). It was, however, expected that there would be divergence of performance in a mallee between the sapling and coppice assessments, on the basis of genetic control of lignotuber development in other eucalypt species (Bortoloto et al 2020;Walters et al 2005;Whittock et al 2003).…”
Section: Genetic Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for the divergent trends in heritability between sites is unclear and may be driven by the different environmental conditions at the three trials and contrasts with the findings from Osorio et al (2001) who found for E. grandis that heritabilities of tree volume and mean annual increments increased from 3 years old until 6 years old (harvest age). It was, however, expected that there would be divergence of performance in a mallee between the sapling and coppice assessments, on the basis of genetic control of lignotuber development in other eucalypt species (Bortoloto et al 2020;Walters et al 2005;Whittock et al 2003).…”
Section: Genetic Parametersmentioning
confidence: 99%
“…The higher differentiation between families postcoppicing at Drummartin seems to be an anomaly and was not repeated at the other two trials. This suggests that another factor is operating and may be explained, in part, by the genetic control of lignotuber development in some eucalypts species (Bortoloto et al 2020;Walters et al 2005;Whittock et al 2003). Walters et al (2005) demonstrated in a nursery experiment that E. obliqua with larger lignotubers had higher concentrations of carbohydrates and after decapitation, produced more above-ground biomass.…”
Section: Genetic Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR product obtained aft er labeling with digoxin was analyzed via 1% agarose gel electrophoresis and recov ered by an agarose gel purification recovery kit [64]. The cells were subsequently pr ehybridized at 37°C for 2 h, depleted of the prehybridization solution, added to the hybridization solution containing a digoxin-labeled probe, and hybridized overnight at 37°C [65]. After hybridization, the membrane was washed twice with 20 mL of 2× SSC and 0.1% SDS solution for 5 min each at room temperature.…”
Section: Qpcrmentioning
confidence: 99%